Effectiveness of Educational Intervention Regarding Polycystic Ovarian Syndrome Among Undergraduate Students of Tanahu - Remana Shrestha; Gayetri Darshandhari (Journal of Karnali Academy of Health Sciences)
Background: PCOS is a complex endocrine disorder characterized by hormonal imbalances, reproductive irregularities, and metabolic disturbances. The overall objective was to find out effectiveness of the educational intervention on knowledge on polycystic ovarian syndrome among undergraduate students.